A Kind of Mending Restorative Justice in the Pacific Islands - Dinnen, Sinclair; Jowitt, Anita; Newton, Tess (ANU Press, 2010)
With their rich traditions of conflict resolution and peacemaking, the Pacific Islands provide a fertile environment for developing new approaches to crime and conflict. Interactions between formal justice systems and informal methods of dispute resolution contain useful insights for policy makers and others interested in socially attuned resolutions to the problems of order that are found increasingly in the Pacific Islands as elsewhere. Contributors to this volume include Pacific Islanders from Vanuatu, Fiji, the Solomon Islands, Papua New Guinea including Bougainville, as well as outsiders with a longstanding interest in the region. They come from a variety of backgrounds and include criminal justice practitioners, scholars, traditional leaders and community activists. The chapters deal with conflict in a variety of contexts, from interpersonal disputes within communities to large-scale conflicts between communities. This is a book not only of stories but also of practical models that combine different traditions in creative ways and that offer the prospect of building more sustainable resolutions to crime and conflict.